Synthesis of polymerizable mono and dihydroxylated phthalocyanines - Alpugan, Serkan (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2013)
Ftalosiyaninler ilginç fiziksel ve kimyasal özellikleri ve uygulama alanlarının genişliği nedeniyle bilimadamlarının ilgisini çekmektedir. Polimer ftalosiyaninler, ısıyla ayarlanabilen özellikleri ve nano boyutta malzeme oluşturabilme açısından önemli bir konudur. Çeşitli polimer düzenleri arasında, ftalosiyaninlerin yan zincir polimerleri pek az incelenmiştir. Bu yüksek lisans tez çalışmasında mono ve dihidroksilli nikel ftalosiyaninler ve europyum double-decker ftalosiyaninler tasarlandı ve hazırlandı. Bu moleküller MALDI, FT-IR, UV-Vis ve NMR spektroskopisiyle karakterize edildi. Double-decker türevleri için yeni ve kolay bir sentez yöntemi geliştirildi.Polimerleştirme için ilk denemeler yapıldı. Anahtar Sözcükler: Ftalosiyanin; double-decker; yan zincir polimer; sentez

Phthalocyanines draw attraction of scientists because of their interesting physical and chemical properties and its wide range of applications. Polymeric phthalocyanines are an important subject because of their tunable properties with heat and their ability to form materials on nano scale. Among the various types of possible polymeric agencements, side-chain polymeric phthalocyanines remains scarcely investigated. In this master thesis, mono and dihydroxylated polymerizable nickel phthalocyanines and europium double-decker phthalocyanines have been designed and prepared. These molecules has been characterized with MALDI, FT-IR, UV-Vis and NMR spectroscopy. In the case of the double-decker derivatives, a new and easy synthetic method has been developed. Preliminary polymerization expriments have been done.
Polimerleştirilebilir mono ve dihidroksilli ftalosiyanin sentezi
Keywords: Kimya; Chemistry; Phthalocyanine; double-decker; side-chain polymer; synthesis